Making China Modern From the Great Qing to Xi Jinping - Klaus Muhlhahn (Cambridge, Massachusetts The Belknap Press of Harvard University Pres, 2019)
Klaus Mühlhahn situates modern China in the nation's long, dynamic tradition of overcoming adversity and weakness through creative adaptation--a legacy of crisis and recovery that is apparent today in China's triumphs but also in its most worrisome trends. Mühlhahn's panoramic survey rewrites the history of modern China for a new generation.-- Provided by publisher
Includes bibliographical references and index.
Keywords: China--History--Qing dynasty, 1644-1912.